Productivity and Well-Being of Broiler Chickens Supplemented With Probiotic - Lima Almeida Paz, Ibiara Correia de [UNESP] (2019)
Efficiency in poultry production is based on the balance between nutrition, intestinal health, and animal welfare. With increasing consumer demand for antibiotic suppression of animal feed for growth, the animal nutrition segment has sought new alternatives to optimize production rates and, based on this concept, use probiotics-living microorganisms (beneficial bacteria and yeast) for animal health. The objective of the experiment was to evaluate the production and welfare of broilers fed different doses of probiotics. A randomized block experimental design with 4 treatments and 10 replicates of 50 birds (400 birds per treatment) each was employed as follows (Table 2): group 1-negative Control (NC): diet with a mixture of chlorohydroxyquino-lines as the growth promoter at all phases; group 2: diet with half a dose of probiotic (HD) and chicks inoculated at the hatchery whit 5 x 10(8)cfu/chick; group 3-positive control (PC): diet with probiotic (dose recommended by the manufacturer) and birds inoculated at the hatchery whit 1 x 10(9)cfu/chick; group 4: diet with probiotic (double the dose) (DD) and birds inoculated at the hatchery whit 2 x 10(9)cfu/chick. The evaluated characteristics were performance, carcass yield and carcass parts, incidence of pododermatitis and myopathy lesions, intestinal quality, and bird welfare. The administration of the probiotic at the commercially recommended dose promotes better results in the performance, carcass yield and parts, and behavior and well-being of the birds.